Czech Bluegrass : Notes from the Heart of Europe - Bidgood, Lee.; Project Muse. (Urbana, IL : University of Illinois Press, 2017)
Bluegrass has found an unlikely home, and an avid following, in the Czech Republic. The music's emergence in Central Europe places it within an increasingly global, network of communities built around bluegrass activities. Lee Bidgood offers a fascinating study of the Czech bluegrass phenomenon, merging intimate immersion in the music with on-the-ground fieldwork informed by his life as a working musician. Drawing on his own personal and professional interactions, Bidgood charts how Czech bluegrass put down roots and looks at its performance as a uniquely Czech musical practice. He also reflects on "Americanist" musical projects and the ways Czech musicians use them to construct personal and social identities. Bidgood sees these acts of construction as a response to the Czech Republic's postsocialist environment but also to US cultural prominence within a global mediascape. Book jacket.
""Cover""; ""Title""; ""Copyright""; ""Contents""; ""Foreword by Tony Trischka""; ""Introduction""; ""1 Place, Meaning, Community, and In-Betweenness""; ""2 Czech Bluegrass Histories and Backgrounds""; ""3 Making Bluegrass at Home, Abroad, and In Between""; ""4 Learning and Playing Americanness on the Fiddle""; ""5 Singing Truth, Fidelity, and Play in Czech Bluegrass Gospel""; ""A Tag: America/Amerika""; ""Notes on Language""; ""Notes""; ""Glossary of Czech Terms""; ""References""; ""Recommended Media""
Description based on print version record.
Includes bibliographical references (pages 143-151) and index.
JSTOR
Keywords: Bluegrass music -- Czech Republic; Bluegrass music -- Europe; MUSIC / Musical Instruments / General; MUSIC / Printed Music / Band & Orchestra; MUSIC / General; Bluegrass music; Czech Republic; Europe